Engulfed : the Death of Paramount Pictures and the Birth of Corporate Hollywood. - Dick, Bernard F. (Lexington : The University Press of Kentucky, 2015)
From Double Indemnity to The Godfather, the stories behind some of the greatest films ever made pale beside the story of the studio that made them. In the golden age of Hollywood, Paramount was one of the Big Five studios. Gulf + Western's 1966 takeover of the studio signaled the end of one era and heralded the arrival of a new way of doing business in Hollywood. Bernard Dick reconstructs the battle that culminated in the reduction of the studio to a mere corporate commodity. He then traces Paramount's devolution from free-standing studio to subsidiary -- first of Gulf + Western, then Paramo.
Cover; Half-title; Title; Copyright; Contents; Preface; 1 Mountain Glory; 2 Mountain Gloom; 3 Barbarians at the Spanish Gate; 4 Charlie's Boys; 5 The Italian Connection; 6 The Diller Days; 7 Goodbye, Charlie; 8 Sumner at the Summit; Epilogue; End Titles; Notes; Index.
Print version record.
JSTOR
Keywords: Paramount Pictures Corporation -- History; Paramount Pictures Corporation; PERFORMING ARTS -- Film & Video -- History & Criticism; History